The Synthesis Of Functionalized-Silica/Carbon Catalysts From Rice Husk For The Conversion Of Hexose Sugar Into Methyl Levulinate And 5-Hydroxymethylfurfural - Syed Abd Kadir, Syed Muhammad Al-Amsyar (2018)
Recently, silica/carbon composite material has received much attention in heterogeneous catalysis due to its unique hybrid properties. However, the difficulties in designing green synthetic methods remain challenging. In this study, varied proportion of silica/carbon heterogeneous catalyst was prepared directly from rice husk by varying the carbonization temperatures (250, 300, 350, 400, and 450 °C). The prepared composites were functionalized separately with sulfonic acid and aluminium oxide giving the following catalysts: sulfonated-silica/carbon (SO3H-SiO2/C-250, SO3H-SiO2/C-300, SO3H-SiO2/C-350, SO3H-SiO2/C-400, SO3H-SiO2/C-450) and silica/carbon-supported aluminium oxide (Al-SiO2/C-350, Al-SiO2/C-400, and Al-SiO2/C-450). For the SO3H-SiO2/C catalysts, the XRD data confirms these composites were amorphous.